Evaluation of the relationship between corpus callosum and internal capsule and tuber load in patients with tuberous sclerosis complex by diffusion tensor imaging - Hacer Cesme, Dilek (Annals of Medical Research, 2021)
Aim: To determine whether there are Diffusion Tensor Imaging (DTI) changes in the white matter pathways such as corpus callosum and internal capsule in patients with Tuberous sclerosis complex (TSC) and to investigate its relationship with tuber load. Materials and Methods: Our study included 17 children with TSC and 15 healthy controls. Total tuber load of the brain was calculated. Correlation between tuber load and ADC (Apparent diffusion coefficient) and FA (Fractional anisotropy) values at corpus callosum (CC) and internal capsule were investigated.Results: When patients with TSC were compared with control, there was a significant difference in ADC and FA values in the corpus callosum and internal capsule. There was a significant difference in FA values between the anterior and posterior limbs of the internal capsule on both sides. The ADC values of CC splenium were positively correlated with the total cerebral tuber load. Also, The FA values obtained from CC splenium were negatively correlated with the tuber load of the right cerebral hemisphere. Conclusion: Relationships between corpus callosum and internal capsule ADC and FA changes and tuber load show that microstructural damage develops in the white matter pathways. DTI parameters can be used as a more sensitive biomarker in the evaluation of the abnormal structure of white matter in patients with TSC. More comprehensive studies are needed to more clearly demonstrate the relationship between DTI properties of white matter and tuber load in TSC patients.